The Effect of Peer Feedback on Students’ Writing - Rosi Anjarwati (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
Writing is one of productive skill which frequently represents students’ ability in expressing their thought toward something. Peer-feedback is considered to be important point in students’ writing process. This article aims to investigate the effect of peer feedback on students’ writing achievement at STKIP PGRI Jombang. Quasi-experimental is used as research design with test as the main instrument and questionnaire as the secondary instrument. The result of ANCOVA showed that there is a significant effect of peer feedback on students’ writing achievement. Moreover, the result of students’ response toward the used of peer feedback indicates positive result